2012
DOI: 10.1016/j.phytochem.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucosinolates on a generalist and specialist leaf-chewing herbivore and an associated parasitoid

Abstract: of Arabidopsis thaliana that differ in their GLS composition and concentrations and one 32 transformed line that constitutively produces higher concentrations of aliphatic GLS were 33 used, the latter allowing a direct assessment of the effects of aliphatic GLS on insect 34 performance. 35Feeding by the generalist S. exigua and the specialist P. rapae induced both higher 36 aliphatic and indole GLS concentrations in the A. thaliana ecotypes, although induction was 37 stronger for indole than aliphatic GLS. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 44 publications
(17 reference statements)
2
45
0
1
Order By: Relevance
“…However, P. rapae larvae were found to develop poorly on high levels of indole glucosinolates such as, neoglucobrassicin [36]. Conversely, another study observed that P. rapae developed more poorly on plant types containing a high concentration of aliphatic glucosinolates [23]. It was suggested that higher concentrations of glucosinolates enhanced expression of the nitrile-specifier protein, thus leading to increased energy costs for P. rapae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, P. rapae larvae were found to develop poorly on high levels of indole glucosinolates such as, neoglucobrassicin [36]. Conversely, another study observed that P. rapae developed more poorly on plant types containing a high concentration of aliphatic glucosinolates [23]. It was suggested that higher concentrations of glucosinolates enhanced expression of the nitrile-specifier protein, thus leading to increased energy costs for P. rapae.…”
Section: Discussionmentioning
confidence: 99%
“…In brassicas, upon tissue wounding-such as chewing, myrosinase is released from damaged vacuoles and degrade glucosinolates, which leads to the accumulation of isothiocyanates, a toxin to insects [22]. However, P. rapae is a specialist insect and produces nitrile-specifier proteins, which degrade the majority of glucosinolates into less harmful nitriles [21]- [23]. Previously, we showed that sinigrin, a specific type of glucosinolate, played a role in shaping microbiota structure in the P. rapae midgut and altered colonization resistance to non-pathogenic invaders [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, hydrolysable tannins in quaking aspen (Populus tremuloides) correlate negatively with immune defense in the autumnal moth Epirrita autumnata (Haviola et al, 2007), and high iridoid glycoside concentrations in P. lanceolata compromise immune responses in the common buckeye caterpillar Junonia coenia (Smilanich et al, 2009). Lower immune defense can lead to higher performance of parasitoids (Reudler et al, 2011;Kos et al, 2012). While microbial root mutualists affect the expression of these (and other) secondary chemicals (tannins, Beyeler and Heyser, 1997; iridoid glycosides, Bennett et al, 2009), to our knowledge, no study has directly explored effects of soil organisms on host insect immunity through changes in secondary chemistry.…”
Section: Prey Qualitymentioning
confidence: 99%
“…Arabidopsis can be converted into a large number of defensive metabolites during herbivory (Halkier and Gershenzon, 2006;Hopkins et al, 2009;Ahuja et al, 2010;Wittstock and Burow, 2010;Bohinc et al, 2012;Kos et al, 2012;Mithofer and Boland, 2012;Rohr et al, 2012;Stauber et al, 2012).…”
Section: Plant Materialsmentioning
confidence: 99%
“…We wondered whether the high mortality seen with control plants might be due to the endogenous glucosinolates produced by Arabidopsis. Glucosinolates are plant secondary metabolites, found in members of the Brassicaceae family, which have insecticidal effects on insect pests such as H. armigera (Hopkins et al, 2009;Muller et al, 2010;Bohinc et al, 2012;Kos et al, 2012;Mithofer and Boland, 2012). Herbivory of Arabidopsis by H. armigera has been shown in induce production of indolic glucosinolates (BadenesPerez et al, 2013) and H. armigera were shown to avoid feeding on the mid-vein and periphery of Arabidopsis rosette leaves where the concentration of the major glucosinolates is highest (Shroff et al, 2008).…”
Section: Resistance Of Transgenicmentioning
confidence: 99%